2010
DOI: 10.1093/bja/aeq133
|View full text |Cite
|
Sign up to set email alerts
|

Critical incident reporting and learning

Abstract: The success of incident reporting in improving safety, although obvious in aviation and other high-risk industries, is yet to be seen in health-care systems. An incident reporting system which would improve patient safety would allow front-end clinicians to have easy access for reporting an incident with an understanding that their report will be handled in a non-punitive manner, and that it will lead to enhanced learning regarding the causation of the incident and systemic changes which will prevent it from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
249
4
20

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(277 citation statements)
references
References 51 publications
4
249
4
20
Order By: Relevance
“…Several studies have shown that healthcare professionals, particularly physicians, agree with the importance of incident reporting and the concept of learning from errors [19,20]. Nevertheless, in practice, many incidents are not reported [20][21][22][23], due to numerous barriers such as non-ergonomic reporting tools, workload, fear of punishment and lack of feedback to the report [22][23][24][25]. In the present study, we were not able to estimate the rate of reported incidents and some incidents were probably not reported.…”
Section: Discussioncontrasting
confidence: 57%
“…Several studies have shown that healthcare professionals, particularly physicians, agree with the importance of incident reporting and the concept of learning from errors [19,20]. Nevertheless, in practice, many incidents are not reported [20][21][22][23], due to numerous barriers such as non-ergonomic reporting tools, workload, fear of punishment and lack of feedback to the report [22][23][24][25]. In the present study, we were not able to estimate the rate of reported incidents and some incidents were probably not reported.…”
Section: Discussioncontrasting
confidence: 57%
“…Data will be an underestimation of true numbers. Underreporting has been attributed to various factors including form design, time constraints, and fear of blame or punitive action, lack of feedback and lack of clarity on what should be reported amongst other reasons [48].…”
Section: Limitationsmentioning
confidence: 99%
“…16,34 There is a fine line between serious adverse events, which measure death, permanent disability and care escalation, and critical incidents. Critical incidents measure a wider variety of events, including "near misses" and have been defined as "any event that affected, or could have affected, the safety of the patient while under the care of an anaesthetist from the induction of anaesthesia until discharge from the post-anaesthesia care unit".…”
Section: Introductionmentioning
confidence: 99%